Reclaiming The Healing Arts of The Ancient Priestess: Babaylanism as Site of Southeast Asian "Feminisms" - Flaudette May V. Datu (Wacana Seni Journal of Arts Discourse, 2012)
This article invokes – as a form of strategic essentialism – the figure of the babaylan, the ancient pre-colonial Philippine priestess as signifier for women's life-giving, nurturing and healing powers. By reclaiming her legacy, I will present the outlines of what could be a possible model for Southeast Asian feminist frameworks. Babaylanism revolves around embodied spirituality – a concept where the body is construed as an anatomical, spiritual, social and psychic space grounded on fluidity and wholeness, instead of hierarchy and dualities. Drawing from my ongoing study and engagement with contemporary women artists in the visual arts of Asia, I will present examples of how selected Indonesian, Philippine and Thai women artists articulate and embody the babaylan in their life and their works.